Like Nature, Industrial Relations Abhors a Vaccum. The Case of the Union-Free Strategy - Barbash, Jack (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
If unionism is not performing the equity fonction, another way will be found to ensure equilibrium in industrial relations. The author examines how management and the State have acted as substitutes.